The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.21303/2504-5571.2022.002261
|View full text |Cite
|
Sign up to set email alerts
|

The scourge of gender-based violence (GBV) on women plaguing South Africa

Abstract: Despite the existence of a constitutional legal framework, criminal sanctions to address violent behaviour by men are not enough. The killing of women by men has reached a disproportionate crescendo in South Africa. It is critical, that as a society we denounce the continuation of this trend and address the underlying causes of violent masculinity and physical abuse against women. Social norms, religious and traditional values, patriarchy, and gender relationships contribute to dominant notions of masculinity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Police were found to not take the participants’ plight seriously. This is congruent with the study of (Yesufu 2022 :97), who identified police as lacking the capacity and sensitivity required to address IPV matters, and that makes victims feel responsible or at fault, thus contributing to secondary victimisation (Gouws 2022 :2; Gumani 2022 :380).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Police were found to not take the participants’ plight seriously. This is congruent with the study of (Yesufu 2022 :97), who identified police as lacking the capacity and sensitivity required to address IPV matters, and that makes victims feel responsible or at fault, thus contributing to secondary victimisation (Gouws 2022 :2; Gumani 2022 :380).…”
Section: Discussionsupporting
confidence: 85%
“…South Africa takes fourth place globally in terms of excessive acts of gendered violence (Yesufu 2022 :96), and this is an extremely concerning position the country finds itself in. Of the various types of gender-based violence (GBV), intimate partner violence (IPV) is a considerably rampant type of GBV (Nguyen et al 2022 :2), and has been found to affect 20% to 50% of women in South Africa (Sere, Roman & Ruiter 2021 :2).…”
Section: Introductionmentioning
confidence: 99%
“…In many jurisdictions, evidence of BWS has been used in criminal trials to support self-defence claims for women and young girls who have harmed or killed their abusers. This defence, in large part, has been based on the argument that the victim's actions were a response to a genuine fear for their life or safety (Yesufu 2022). At the same time, the admissibility and weight given to BWS evidence in legal proceedings vary by jurisdiction.…”
Section: Battered Woman Syndrome (Bws)mentioning
confidence: 99%
“…GBV in South Africa has reached extreme and crisis proportions (Clark, 2020;Yesufu, 2022). It continues to make news headlines in South Africa despite the government's efforts to curb it.…”
Section: Overview Of Gender-based Violencementioning
confidence: 99%